PENERAPAN SISTEM KANBAN UNTUK MENGURANGI OVERPRODUKSI PADA PART HVAC D26A LHD BV DENGAN METODE JUST IN TIME DI PT. XYZ - Febrio Musriyanto (Journal of Industrial and Engineering System, 2025)
This research aims to reduce overproduction of D26A LHD BV HVAC parts at PT. XYZ by implementing the Kanban system using the Just In Time (JIT) method. Overproduction is a significant problem that causes the buildup of goods in warehouses and increases storage. By implementing the Kanban system, it is hoped that production can be controlled according to actual demand, thereby reducing waste. The results of research in July showed that after implementing the kanban system, overproduction was reduced drastically by 99.38%, from 814 units to only 5 units on July 31 2023. In addition, production time efficiency also increased significantly. In July 2023, efficiency increases from 9.77% to 81.68%. However, implementing this system is not without challenges, including the need for overtime on some dates to adjust production flow. The need for overtime occurs on July 13 2023 for 1.19 hours per day and July 17 – 19 2023 for 2.76 hours. This research concludes that the Kanban system is effective in reducing overproduction and increasing production efficiency at PT. XYZ. However, to achieve optimal implementation, regular evaluation, employee training, system adjustments based on feedback, and better overtime management are needed. With these steps, PT. XYZ can further optimize the implementation of the kanban system, increasing operational efficiency and reducing overall production costs